Economic Analysis of New Product (Gas for Absorption Chiller in Commercial Segment Customer) - Wisnu Haryadi; Yulita Fairina Susanti (Sekolah Tinggi Manajemen IPMI, 2019)
The purpose of this is toevaluates a new product called GasCool that will be implemented by the company before this product launch to the costumer. This new product is a solution for the PT Perusahaan Gas Negara, Tbk (“PGN”) to manage their declining revenue in commercial customer segment in the last 4 years. This study used an economic analysis to evaluates GasCool using three parameters. The parameters consist of Net Present Value, Internal Rate of Return and Payback Period.The result indicates that GasCool is feasible to be implemented and sell to the commercial segment customer. The economic analysis has shown that selling GasColl will generate17.6% Internal Rate of Return and 5.5 years Payback Period. Furthermore, the Net Present Value from selling GasCool is Rp10,4 billion in 10 years of implementation and the discount rate for economic analysis is 8.2%.